Predictors of Virological Failure in HIV Patients Receiving FirstLine Antiretroviral Therapy with Good Adherence - Kurniawan, Farid; Djauzi, Samsuridjal; Yunihastuti, Evy; Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Antiretroviral therapy (ART) effectively suppress HIV replication. Viral load (VL) measurement is better predictor than clinical or immunological criteria to evaluate success or failure of ART. However, in country with limited resources, viral load measurement is not easily accessible by HIV patients receiving ART. Therefore, it is necessary to know which factors that can predict virological failure. In previous studies, adherence was an important factor for suppression of HIV viral load. This study is aimed to know predictors of virological failure in HIV patients receiving recent first line ART regimen with good adherence in Indonesia. Methods. A retrospective cohort study was conducted among adult HIV patients in Out-patient Clinic of Cipto Mangunkusumo Hospital that started ART during periode of January 2011-June 2014. HIV patients with good adherence that had viral load data 6-9 months after initiation of ART were included in this study. Virological failure was defined as viral load ≥ 400 copies/ mL after minimum of 6 months therapy with good adherence. Age at starting ART, risk factor for HIV infection, HIV clinical stage, HIV-TB co-infection, baseline CD4 value, CD4 count increase, baseline hemoglobin level and body mass index, weight changes during therapy, and ART based regimen were analyzed in this study. Results. A total of 197 patients were included in this study. Virological failure was found in 21 patients (10,7%). CD4 increase /mm3 after minimum 6 months of ART was predictor of virological failure (p = 0,003; OR 5,802, 95%CI 1,842-18,270). Conclusion. CD4 increase /mm3 after minimum 6 months therapy can predict virological failure in HIV patients receiving first line ART with good adherence